Analysis of Proximates, Organoleptics, and Saving Power of Fortified Wet Noodles Curcuma domestica and Alpinia purpurata K. Schum. - Kamelia, Marlina; Kurnia, Aniza; Supriyadi (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
The storability of wet noodles is generally very low because it has a high water content. This can cause losses to the wet noodle sellers so that these problems are often overcome using chemicals as preservatives. But this in the long run can cause health problems. Therefore, the aim of this study is to increase the shelf life of wet noodles by using natural preservatives in combination with Curcuma domestica and Alpinia purpurata K. Schchum. This research is an experiment that was designed with a Completely Randomized Design (CRD) with 4 treatments, namely control (P0) and 3 combinations of Curcuma domestica and Alpinia purpurata K. Schchum 5%: 15% (P1); 10%: 10% (P2); and 15%: 5% (P3), each of which was repeated 4 times. Wet noodle samples were then performed Proximate Test, Organoleptic Test, and Microbiology Test (TPC and Mold/Yeast). The data obtained were then tested for ANOVA and continued with a LSD test with a value of α = 5%. The results of the wet noodle test with the addition of a combination of CCurcuma domestica and Alpinia purpurata K. Schchum showed proximate levels according to the SNI stipulations. The best organoleptic wet noodle test results are P2 treatment. In the TPC cup count results and the total mold/yeast combination of Curcuma domestica and Alpinia purpurata K. Schchum the best treatment is also found in the P2 sample which can increase the storability of wet noodles up to 48 hours which appears in the total microbial and mold / yeast does not exceed the maximum limit of the provisions SNI.